MK2 Is Required for Neutrophil-Derived ROS Production and Inflammatory Bowel Disease - Zhang, Tao; Jiang, Junhang; Liu, Jingting; Xu, Lu; Duan, Shixin; Sun, Lei; Zhao, Wenjuan; Qian, Feng (Frontiers in Medicine, 2020)
Inflammatory bowel disease (IBD) is a chronic disease that is commonly accompanied by increased inflammatory responses and elevated reactive oxygen species (ROS) of the gastrointestinal tract. Here, we found that MAPK-activated protein kinase 2 (MK2) modulates ROS production and is required for dextran sulfate sodium (DSS)-induced IBD in the mouse model. Genetic ablation of MK2 in the myeloid lineage cells (MK2Lyz2−KO) protected against DSS-induced colitis injury. In response to DSS challenge, compared to MK2lyz2−WT mice, MK2Lyz2−KO mice exhibited less damage of epithelial and goblet cells, decreased generation of interleukin (IL)-6, tumor necrosis factor (TNF)-α, and ROS, as well as reduced Ki67-positive cells and concentrations of myeloperoxidase (MPO) in the intestinal epithelium. Furthermore, upon treatment with formylated peptide N-formyl-methionyl-leucyl-phenylalanine (fMLF), the generation of ROS was attenuated in MK2-deficient neutrophils, in which the phosphorylation of Akt and p38 MAPK was also reduced. Collectively, these findings indicated that MK2 is required for neutrophil-derived ROS production and IBD, and MK2 and ROS are promising therapeutic targets for IBD.